Dimethylfumarate inhibits microglial and astrocytic inflammation by suppressing the synthesis of nitric oxide, IL-1β, TNF-α and IL-6 in an in-vitro model of brain inflammation - Wilms, Henrik; Sievers, Jobst; Rickert, Uta; Rostami-Yazdi, Martin; Mrowietz, Ulrich; Lucius, Ralph (Journal of neuroinflammation, 2010)
Brain inflammation plays a central role in multiple sclerosis (MS). Dimethylfumarate (DMF), the main ingredient of an oral formulation of fumaric acid esters with proven therapeutic efficacy in psoriasis, has recently been found to ameliorate the course of relapsing-remitting MS. Glial cells are the effector cells of neuroinflammation; however, little is known of the effect of DMF on microglia and astrocytes. The purpose of this study was to use an established in vitro model of brain inflammation to determine if DMF modulates the release of neurotoxic molecules from microglia and astrocytes, thus inhibiting glial inflammation.
Gesehen am 26.02.2024